Adsorption isotherms, kinetics and mechanism of Pb(II) ions removal from aqueous solution using chemically modified agricultural waste. (24th January 2013) - Senthil Kumar, P.; Senthamarai, C.; Sai Deepthi, A.S.L.; Bharani, R.
Abstract The removal of Pb(II) ions from aqueous solution by chemically surface modified Strychnos potatorum seeds (SMSP) was investigated. The surface modification of the adsorbent was confirmed by the FTIR and SEM analyses. The Freundlich adsorption isotherm model provides a better fit to the adsorption isotherm data. The maximum adsorption capacity of SMSP for Pb(II) ions was found to be 166.67 mg/g at optimum conditions of pH 5.0, contact time of 30 min, SMSP dosage of 2 g/L and temperature of 30°C. The adsorption kinetics for Pb(II) ions removal by the SMSP follows the pseudo‐second order kinetic model. Adsorption mechanism of Pb(II) ions onto the SMSP was explained with the intraparticle diffusion, Boyd kinetic and Shrinking core models (SCM). The effective diffusivity values were calculated from the Boyd kinetic model: 7.723 × 10−12, 8.464 × 10−12, 6.877 × 10−12, 8.358 × 10−12 and 6.983 × 10−12 m2/s for the initial Pb(II) ions concentration from 100 to 500 mg/L, respectively. The diffusivity values were estimated from the SCM: 8.901 × 10−9, 8.586 × 10−9, 8.359 × 10−9, 5.368 × 10−9 and 4.318 × 10−9 m2/s for the initial Pb(II) ions concentration from 100 to 500 mg/L, respectively. The results suggest that SMSP can be used as an effective low‐cost adsorbent for the Pb(II) ions removal.